ロケット ニヨル ジバ カンソク b. デンバ ト デンリュウ ケイ ダイ1カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 1 - 遠山, 文雄; トオヤマ, フミオ; 青山, 巌; アオヤマ, イワオ; 小松, 誠一; コマツ, セイイチ; TOHYAMA, Fumio; AOYAMA, Iwao; KOMATSU, Seiichi (国立極地研究所, 1979)
P(論文) 南極昭和基地で打ち上げられた,S-210JA-24および25号機に搭載された磁力計により磁場測定が行われた.両ロケットともオーロラ出現時に打ち上げられ,電流にともなう磁場変動を検出した.搭載されたフラックスゲート型磁力計は,新しい方式の三成分同時測定装置で,0.2秒毎にサンプリングされたデータがディジタル出力されるため,高度に関して分解能の高い磁場変動プロファイルが得られた.その結果によると,24号機では,高度約110 kmからロケットの最高高度(約118 km)にかけて大きな磁場変化が認められた.さらに,地磁気姿勢計によるロケットの姿勢解析結果を報告する. Detailed observations of geomagnetic field variation in and near the aurora were provided by the new three-axis flux-gate magnetometer experiments acquired with two sounding rockets (S-210JA-24 and 25) that were launched on August 17 and September 1, 1976 at Syowa Station, Antarctica. The magnetometers were sampled at a rate of 5 samples per axis per second. The magnetic differences were obtained by subtracting the extrapolated values of the IGRF 1975.0 from the measured values. The experiment with the JA-24 rocket exhibited a pronounced increase in magnitude with the increase in height from 110 km to the apogee of the vehicle (118 km). The result of the analysis of rocket attitudes with the geomagnetic aspect sensor are also discussed. departmental bulletin paper